On Intimacy and Design - Ramona Albert; Christopher Johnson (Oz, 2011)
Most people have a favorite object. Even if one rejects materialism and tangible goods, or even if one doesn’t realize it or can’t express it, the lives of all people are made more enjoyable, pleasurable, or enriched if even just a little bit, by a particular small-scale object. This object might be a toy, or a piece of clothing, or a type of tool maybe.